ANTI-INFLAMMATORY ACTIVITY OF PEGAGAN LEAVES (Centella asiatica (L.) Urban) EXTRACT CREAM - Mardiyah, Siti (Journal Pharmaceutical Science and Application; Vol 4 No 1 (2022): Journal Pharmaceutical Science and Application, 2022)
Background: Pegagan leaves (Centella asiatica (L.) Urban) is an herbal plant family of Apiaceae containing the active ingredients of the triterpenoid group glycosides (asiaticoside, Asiatic acid, madekasat acid, madikassosida) centelloside, flavonoids, and Asiatic acids. Inflammation is a complex reaction in tissues that involves a response to blood vessels and leukocytes. Objective: The purpose of this study was to find out the anti-inflammatory activity that occurs in the legs of mice in the form of preparation of pegagan extract cream (Centella asiatica (L.) Urban). Methods: Pegagan extract is done by the maceration method that uses ethanol 70%. Test animals used to squeak white males as much as 10 heads with a body weight of 20-30 grams. Animals test were divided into 5 treatment groups, namely the pegagan extract group with a dose of 2 g/kg BB; 4 g/kg BB; 6 g/kg BB, positive control (Betason cream 0.1%), and negative control (pegagan extract 2 g/kg BB). 1 hour before treatment of squeaky soles is inducted with a 1% carrageenan solution subplantarically. Results: Measurement of edema volume on the soles of the feet of mice is observed every 1 hour for 6 hours. The results showed that pegagan extract cream with a dose of 6 g / kg BB showed the maximum percentage of inhibition edema that is at the 6 hours with a result of 80,2%. The results of the data analysis of the percentage of inhibition of Centella asiatica extract from the treatment group Negative Control-Formula II and Negative Control-Formula III showed significant differences (p<0.05). Conclusion: Pegagan leaves extract has an anti-inflammatory effect on the feet of mice. Keywords: Anti-inflammatory, Pegagan leaves, Centella asiatica (L.) Urban